Exploring the potential link between vegetable oil supplementation and adverse food reactions in dogs: a preliminary study - Elisa Maina; Eric Cox (BMC Veterinary Research)
Abstract Background Adverse food reactions (AFR) are a common cause of skin diseases in dogs, with a prevalence of up to 24%. Research in humans and mice has shown that a high intake of vegetable oils rich in omega-6 polyunsaturated fatty acids (n-6 PUFA) can increase the risk and severity of allergic diseases. This study aimed to investigate the association between AFR and the supplementation of vegetable oils in the canine diet. Results A total of 459 dogs were analyzed, with atopic dermatitis (22.66%) and adverse food reactions (AFR) (8.06%) being the most common diagnoses. Oil supplementation was recorded in 14.16% of dogs, with extra-virgin olive oil being the most common (70.77%). Dogs with AFR and concurrent AFR and CAD showed significantly higher oil supplementation rates compared to other conditions (P < 0.05; P < 0.001). No significant association was found between oil type and diagnosis (P = 0.563). After excluding EFA-supplemented dogs and those on prescription dermo diets, oil supplementation was still more prevalent in dogs with AFR compared to other conditions (29.31% vs. 10.10%, P < 0.001). Conclusions Vegetable oil supplementation was more frequent in dogs with AFR than in those with other dermatological conditions. This is the first study to evaluate the relationship between vegetable oil supplementation and AFR in dogs. While vegetable oil supplementation is associated with AFR, further studies are needed to establish causality and better understand the role of n-6 PUFA in the development of food allergies in dogs.